2021
DOI: 10.1021/acs.nanolett.0c02558
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidics for Simultaneous Size and Charge Profiling of Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are cell-derived membrane structures that circulate in body fluids and show considerable potential for noninvasive diagnosis. EVs possess surface chemistries and encapsulated molecular cargo that reflect the physiological state of cells from which they originate, including the presence of disease. In order to fully harness the diagnostic potential of EVs, there is a critical need for technologies that can profile large EV populations without sacrificing single EV level detail by av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…This observation also matched with differential movements of EVs and LDLs seen in electrophoretic measurements 22 . At the physiological pH (7.4), the computed σ values were -3.6 mC/m 2 for (V)LDLs and -6.2 mC/m 2 for cancer EVs, whose values agreed with previous reports 23 , 24 . We also found that a slightly acidic pH maximizes the charge difference between EVs and (V)LDL ( Figure 2 C ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This observation also matched with differential movements of EVs and LDLs seen in electrophoretic measurements 22 . At the physiological pH (7.4), the computed σ values were -3.6 mC/m 2 for (V)LDLs and -6.2 mC/m 2 for cancer EVs, whose values agreed with previous reports 23 , 24 . We also found that a slightly acidic pH maximizes the charge difference between EVs and (V)LDL ( Figure 2 C ).…”
Section: Resultssupporting
confidence: 89%
“…Cancer EVs were most negatively charged. Symbols indicate σ values (pH 7.4) reported in other studies for EVs (◼) 24 and for LDLs (▲) 23 . (C) The estimated σ differences between EVs and (V)LDLs were plotted.…”
Section: Figurementioning
confidence: 99%
“…The device fabrication protocol is described in detail in ref. 18,19 and 27 To summarize, we use photolithography followed by reactive ion etching (RIE) to define the fluidic channel (the slit) on a borosilicate glass wafer. Electron beam lithography followed by RIE is then used to create the nanofluidic cavities.…”
Section: Methodsmentioning
confidence: 99%
“…Such approaches average over at least 10 EVs bound per bead or surface element. , A third wave of technologies has extended existing fluorescence-based single-cell and single-molecule analytical approaches to perform individualized EV analysis. Nano flow cytometry can now profile populations of 1000s of EVs down to 100 nm in size stained for a limited number of surface biomarkers. , Alternatively, single EVs can be surface immobilized and then exposed sequentially to a series of fluorescent antibody probes targeting specific markers, achieving higher multiplexing and signal at the expense of throughput. This latter approach has been extended to the detection of EV-encapsulated RNA via fusing of surface bound EVs to liposomes containing molecular beacon probes that hybridize to given RNA/microRNA targets .…”
Section: Introductionmentioning
confidence: 99%